2004
DOI: 10.1007/s00249-003-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural themes in ion channels

Abstract: The recent crystal structure of the prokaryotic inwardly rectifying potassium channel, KirBac1.1, revealed for the first time the structure of a K+ channel in the closed state plus the location of the activation gate. Comparison of the KirBac1.1 structure with other known ion channels reveals a number of common structural features. These common characteristics include the formation of the ion conduction pathway at the interface between adjacent subunits, non-fixed charges forming part of the ion pathway, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…6C, n ϭ 5, p Ͻ 0.001) is consistent with the notion that Glu-316 and Glu-320 play a role in concentrating cations near the periplasmic pore entrance (5,16). Thus, CorA appears to utilize at least one type of electrostatic sink, a property that it shares with numerous other ion channel and transporter proteins (46).…”
Section: Structure-function Relationships In Tmcorasupporting
confidence: 80%
“…6C, n ϭ 5, p Ͻ 0.001) is consistent with the notion that Glu-316 and Glu-320 play a role in concentrating cations near the periplasmic pore entrance (5,16). Thus, CorA appears to utilize at least one type of electrostatic sink, a property that it shares with numerous other ion channel and transporter proteins (46).…”
Section: Structure-function Relationships In Tmcorasupporting
confidence: 80%
“…Together with the analyses of results from mutational studies it has been concluded that K + symporter families from prokaryotes and eukaryotes have evolved from the prokaryotic K + channel proteins (Durell et al, 1999;Durell & Guy, 2001). The findings were used to clone and overexpress a few additional bacterial proteins (as done for KcsA) and to generate their crystal structure in order to understand the general principle of ion channels (see review by Doyle, 2004). The results of experimental data (Meuser et al, 2001) support the conclusion that the crystal structure of the tetrameric KcsA does not present the 'open state', as initially concluded (Doyle et al, 1998).…”
Section: Introductionmentioning
confidence: 73%
“…One such implication is that the ion transport sites of NKCC, although distinct kinetically, may be capable of interacting with one and another through certain key residues. Indeed, the structural models of the tm2-cs1a region also predicts that residues 216 and 220 (Ile and Ile in saA and Val and Leu in saF) are adjacent to one another on the same vertical axis of the ␣-helix, suggesting that their peptide backbones and/or aliphatic R groups are connected through H atoms (35,36). In the case of NKCC, for which ions are proposed to move single file down a translocation pocket (19 -21, 24, 25), such physical interactions could represent a key aspect of the carrier's modus operandi, accounting, in particular, for the kinetic interdependence of the ion binding sites.…”
Section: Discussionmentioning
confidence: 99%